2018
DOI: 10.1186/s12884-018-1871-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors promoting or inhibiting normal birth

Abstract: BackgroundIn response to rising rates of medical intervention in birth, there has been increased international interest in promoting normal birth (without induction of labour, epidural/spinal/general anaesthesia, episiotomy, forceps/vacuum, or caesarean section). However, there is limited evidence for how best to achieve increased rates of normal birth. In this study we examined the role of modifiable and non-modifiable factors in experiencing a normal birth using retrospective, self-reported data.MethodsWomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 49 publications
1
45
1
3
Order By: Relevance
“…Our findings highlighted a lack of midwifery confidence and skill that can be traced back to the training and practice of UK midwives within predominantly obstetric-led services. Numerous surveys and papers have demonstrated this over the last 30 years since Robinson’s pioneering research on the loss of traditional midwifery skills in the 1980s26–29.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings highlighted a lack of midwifery confidence and skill that can be traced back to the training and practice of UK midwives within predominantly obstetric-led services. Numerous surveys and papers have demonstrated this over the last 30 years since Robinson’s pioneering research on the loss of traditional midwifery skills in the 1980s26–29.…”
Section: Discussionmentioning
confidence: 97%
“…All women in this study said they wanted to stay active during labour and give themselves the best opportunity to have a VBAC. These findings are echoed in the qualitative interviews from the USA by Hall et al (2018) who found that women wished for freedom of movement and comfort as strategies for labour and this was also found to increase the probability of normal birth [65, 66].…”
Section: Discussionmentioning
confidence: 93%
“…According to a study on 284 Nigerian nulliparous women in which 74.8% of the parturient gave birth by vaginal delivery, normal birth weight was a factor associated with vaginal delivery [33]. In Prosser's study in which 28.7% of women had a normal delivery, predictors of NVD were multiparity, younger age, spontaneous labor, lower gestational age, knowing the midwives before labor and childbirth, and receiving continuity of care during labor and birth [34].…”
Section: Discussionmentioning
confidence: 99%